ETHOS, PATHOS, LOGOS DAN KOMUNIKASI PUBLIK: A SYSTEMATIC LITERATURE REVIEW - Meidy Aisyah (Jurnal Darma Agung, 2022)
Aristotle's rhetorical theory is one of the oldest communication theories. Aristotle's rhetoric is concerned with 'argument', which seeks to persuade an audience especially in the context of public communication. This journal aims to see the trend of Aristotle's rhetorical studies, categorize them based on the concept of artistic proofs and based on the topic of study, as well as to develop (purify) based on the assumptions of classical rhetoric theory using the Systematic Literature Review (SLR) method. We found that rhetorical theory studies by Aristotles are dominated by political communication topics. This journal also found a decrease in the number of studies using Aristotle's rhetorical theory. We argue that the character of rhetorical theory, which is considered "old-fashioned" and does not have clear guidelines, becomes an obstacle in the analysis process of a study that uses this rhetorical theory. Although most of the article studies mentioned the definition of the concept of artistic proofs correctly, in-depth analysis using artistic proofs was not found. We also found a misunderstanding of Aristotle's rhetorical theory that was less precise and did not look at the historical theory development in several selected journals.